Physical association and coordinate function of the H3 K4 methyltransferase MLL1 and the H4 K16 acetyltransferase MOF. - Dou, Y; Milne, T; Tackett, A; Smith, E; Fukuda, A; Wysocka, J; Allis, C; Chait, B; Hess, J; Roeder, R (2005)
A stable complex containing MLL1 and MOF has been immunoaffinity purified from a human cell line that stably expresses an epitope-tagged WDR5 subunit. Stable interactions between MLL1 and MOF were confirmed by reciprocal immunoprecipitation, cosedimentation, and cotransfection analyses, and interaction sites were mapped to MLL1 C-terminal and MOF zinc finger domains. The purified complex has a robust MLL1-mediated histone methyltransferase activity that can effect mono-, di-, and trimethylation of H3 K4 and a MOF-mediated histone acetyltransferase activity that is specific for H4 K16. Importantly, both activities are required for optimal transcription activation on a chromatin template in vitro and on an endogenous MLL1 target gene, Hox a9, in vivo. These results indicate an activator-based mechanism for joint MLL1 and MOF recruitment and targeted methylation and acetylation and provide a molecular explanation for the closely correlated distribution of H3 K4 methylation and H4 K16 acetylation on active genes.